System dynamics modelling of integrated urban clean water management: A case study in Padang City, Indonesia - Arbi, Yaumal; Ramadhianty, Rumia; Rahayu, Shinta; Putri, Widia (Journal of Engineering Researcher and Lecturer, 2025)
Access to clean water is essential for human life and a key target of Sustainable Development Goal (SDG) 6: Clean Water and Sanitation. However, cities in developing countries, including Padang City, Indonesia, face significant challenges in meeting the growing demand due to population growth and limited water infrastructure. This study used system dynamics modelling approach with Powersim Studio 10 to develop an integrated clean water management system for Padang City. The model simulates the dynamics of population growth, water consumption, production, and distribution efficiency over a 20-year period (2022–2042). Several policy scenarios—optimistic, moderate, and pessimistic—were tested to evaluate their impact on water availability. The baseline scenario predicts a continuous decline in clean water supply due to increasing population, high leakage rates (11.99%), and water wastage (2%), which surpass the water production growth rate (5.01%). As a result, a water deficit is expected. However, under the optimistic scenario, with increased production (10%), reduced leakage (8%), and reduced wastage (3%), Padang City could achieve a clean water surplus by 2042. The moderate and pessimistic scenarios still result in a deficit. This research highlights the value of the system dynamics modelling in forecasting urban water demand and assessing policy impacts. The findings emphasize the need for integrated planning, combining technical solutions and behavioural change, to ensure sustainable water management and support the achievement of SDG 6.